Analysis of Medicine Logistics Management in the Pharmacy Installation of Malinau District Hospital - Ngir, Eric Frada HR; Suharno, Suharno; Fatimah, Fatia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The availability of medicines in hospitals is very important for patient survival, this is because almost 90% of health service interventions in hospitals depend on the use of medicines. The occurrence of medicine shortages, stockpiles that have accumulated, expiration will have an impact medically and economically. Things like this require efficient and effective medicine management efforts through a management system. The purpose of this study was to determine drug logistics management in hospitals starting from the input, process, and output stages at the pharmacy installation at Malinau Hospital. The reason for choosing this location is because the availability of medicines is a variable that has a significant satisfaction score, it is necessary to carry out an analysis of drug logistics management to ensure this. This research is descriptive qualitative research with a management system theory approach based on data obtained from 6 research informants, consisting of the head of the pharmacy installation, coordinator of inpatient pharmacist, coordinator of outpatient pharmacy services, the person in charge of pharmacy warehouse, and 2 warehouse staff pharmacies. Based on the input stage in the form of the availability of pharmaceutical human resources, it is sufficient, the budget using APBD and BLUD is sufficient. The stages of the process consisting of planning needs, medicine procurement, and medicine distribution have been carried out properly. As for the storage and disposal of medicines, management is still found to be ineffective and efficient. At the output stage, the availability of medicines has not been carried out properly, because there are still empty medicine stocks and expired medicines have been found piled up in warehouses that have not been destroyed. Thus it is suggested that the pharmaceutical installation at Malinau Hospital pay more attention to the medicine logistics management system so that it is more effective and efficient. Thus it is suggested that the pharmaceutical installation at Malinau Hospital pay more attention to the medicine logistics management system, especially regarding the quantity and quality of human resources and infrastructure to be further improved.